Social Solidarity and Herbert Spencer: Not the Oxymoron That Might Be Assumed - Offer, John (Frontiers in Sociology, 2019)
This article attempts to retrieve important aspects of Spencer’s sociology from the general neglect and misrepresentation which threatens to overwhelm it all. It does touch in passing on many such highly dubious contentions as that he was a ‘social Darwinist’, but the prime focus is to deal with three linked themes. First, the article examines the significance of his attribution to individuals of ‘social self-consciousness’ as part of sociality, thus distancing it from Durkheim’s influential but suspect reading of Spencer’s individuals as egoistic. Second, it rescues his concept of ‘the social organism’ from misinterpretation. His own writings show it to be a more rigorous and suggestive attempt to configure the morphology of ‘the social’ than commonly assumed. Third, it reconstructs the status of his contrast between ‘militant’ and ‘industrial’ social forms as a contrast between different but more general forms of social life that those descriptions in fact register. With the focus on these three linked themes the article improves the historical accuracy of our understanding of Spencer’s sociology. It also repositions key aspects of it as not alien, quaint and a spent force, but ontologically challenging and possibly prescient for debates about the meaning of ‘the social’ today.